Why Teach the Composition of the Pentateuch? It's Complicated, but Necessarily So - Yoo, Philip Y. (Teaching theology and religion, 2025)
This article explores three issues in teaching the Pentateuch, namely its composition, its place in the history of ancient Israel, and our responsibilities to its past and present interpreters. Although the certainties are few and new ideas and theories emerge, attending to these issues fosters a decentering of the biblical text and invites future interpreters to appreciate the diversity that underlies the Pentateuch.